EVALUATING THE EFFICIENCY OF SOME NANOPARTICALS IN INHIBITING THE GROWTH OF SCLEROTINIA SCLEROTIORUM (LIB) DEBARY, THE CAUSE OF EGGPLANT WHITE MOLD DISEASE IN LABORATORY CONDITIONS: EVALUATING THE EFFICIENCY OF SOME NANOPARTICALS IN INHIBITING THE GROWTH OF SCLEROTINIA SCLEROTIORUM (LIB) DEBARY, THE CAUSE OF EGGPLANT WHITE MOLD DISEASE IN LABORATORY CONDITIONS (Iraqi Journal of Market Research and Consumer Protection, 2026)
This experiment was applied in the Plant Diseases Laboratory/ Postgraduate Studies/ Department of Plant Protection /College of Agricultural Engineering Sciences/ University of Baghdad. Four isolates of Sclerotinia sclerotiorum (Lib) DeBary were collected from infected eggplant grown in different greenhouses in Baghdad Governorate. The pathogenicity of isolates was studied in greenhouse conditions, and the results showed that all isolates were pathogenic. All isolates were identified molecularly using the specialized primers SSFWD, the isolate SR7 was registered at the National Center for Biotechnology Information (NCBI) under accession numbers OR711897.1. The enzymatic activity of the isolates was tested, and isolate SR7 was the most active. The effect of silica, copper and magnesium oxides as nanoparticales on the growth of fungal hyphae of Sclerotinia sclerotiorum (Lib) DeBary was tested at two concentrations of 0.2 and 0.5 g/L in laboratory conditions. The nanoparticale copper oxide was superior in both concentrations with an inhibition rate of 100%, with significant differences from the nanoparticale silica and magnesium oxides, where the inhibition rate in the first concentration reached 36.3 and 50.5%, respectively, while in the second concentration it reached 61.1 and 64.2%, respectively.